Utilization of Soy Protein Isolates in the Production of Chocolates and Chocolate Beverage Powders - Hussin, Norma (1997)
Soy protein isolates (SPI) were incorporated in chocolate and chocolate beverage powders with the objectives of (i) increasing the protein content of the products, (ii) studying their effects on physical, chemical and sensory properties, and (iii) detennining the chocolate stability during storage. Protein contents of chocolates with 5%, 10%, 15% and 20% SPI increased by 2.40%, 4.87%, 7.37% and 9.14% (wb), respectively, when compared to the control. From the amino acid profile, SPI-chocolates had low methionine content (25.12 mglg protein) but still closed to the control (27.55mglg protein), while high lysine content (60.01 mg/g protein) when 10% was added. The contents of other types of amino acid were almost similar to those of control. Sensory evaluation results showed that chocolates with 5% SPI was the most acceptable, while 10% and 1 5% SPI were moderately acceptable. However 20% SPI was unacceptabJe because of its powdery flavour and white crystal (bloom) formation. SPI has the capability of preventing the bloom formation in chocolate, especially 7.5% SPI. The Totox Value (TV) of all chocolates was found to be highest at week 3, while the lowest level was at week 10 when 10% SPI was used. During storage, all chocolates slightly increased in hardness and darker in colour. Response Surface Methodology (RSM) was then applied in experimental design in order to study the physical effects of alkalized cocoa powder (ACP) and soy lecithin (SL) on chocolate beverage powders (CBPs). As a result, the best physical effect of SL on CBPs was around 2-4%, while for ACP, it was found to be at 20%. SPI-Chocolate beverage powders (SCBPs) were produced from a mixture of the optimum levels of ACP (20%) and maximum level of SL (4%). Control and SCBPs with 10-60% SPI had a lower sedimentation (0.46% and 0.58-0.88%, respectively) than SPI and SCBPs singly (14.17% and 2.08%, respectively). SPI completed the wettability test faster than CBPs (62.23 sec and 303.90 sec, respectively). This showed that addition of more SPI can accelerate the wettability of SCBPs. CBPs had higher solubility (67.13%) than SPI (34.13%), thus the incorporation of SPI had reduced the solubility of SCBPs. The overall acceptability of the control and, 10% and 20% SPI were highly accepted, while 30% and 40% SPI were moderately accepted, but 50% and 60% SPI were rejected due to the creamy texture, high viscosity, and high soy flavour. SCBPs were accepted at 10-40% SPI levels and contained 20.70-40.85% (db) of protein. With the addition of up to 30% SPI, the methionine content decreased (20.24 mg/g protein) but it was still closed to the control (24.46 mg/g protein). Lysine content increased up to 30.20 mg/g protein as compared to the control (12.76 mg/g protein).